A Survey on Improved Canny-Edge Detection Algorithm - Sabah, Mohammed; Sundaraguru, R (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
In this paper we propose to study various papers and article which are based on edge detection algorithm and analyze each one of them. Edge detection is a very important technique in image Processing. Edge detection is used to detect the boundaries of objects within images. It works based on principle of detecting discontinuities in an image. Edge detection is used for image segmentation and data extraction in domains such as image processing, computer vision, and machine vision. There are various algorithms existing in order to perform edge detection such as Robert, Prewitt, Sobel, Zero-Cross, and Marr-Hildreth. All these are suitable for different conditions and situation. Out of all canny edge detection has the capability to work and is adaptable to various environmental conditions. After John Canny introduced a canny algorithm, many problems were faced during real-time implementation in FPGA/CPLD, hence many research and finding were done by many scholars and they came up with an improved canny algorithm which solved the complexity of the algorithm and helped in implementing real-time applications.